Potential sources of chemopreventive agents from Indonesian plants against colorectal cancer: A review - Maria Immaculata Iwo, Muhammad Andhika Alfaridzi, Hubbi Nashurullah Muhammad (Journal of Applied Pharmaceutical Science, 2023)
Colorectal cancer (CRC) is a serious health problem worldwide. The ever-increasing cases encouraged researchers to discover more effective novel drugs from plant sources. In this review, we summarized the plants contributing to the chemoprevention of CRC, as reported in in vitro animal studies and clinical trials. A literature search was conducted to collect information regarding the biological activities of plants from PubMed and Google Scholar, and also hand searching from other literature databases. 77 plants of 47 families cultivated in Indonesia were introduced as candidates for chemopreventive agents that help reduce cancer proliferation, progression, or recurrence. Phenolic compounds were revealed to have anticancer effects in most studies. Allium sativum L., Zingiber officinale Roscoe, Annona muricata L., and Camellia sinensis (L.) Kuntze, the fourth Indonesian plant only in a clinical trial, was able to reduce the risk of recurrence of colon adenoma, safe, and tolerated. Therefore, this review article could be key to conducting clinical trials on other plants to evaluate the safety and efficacy of developing new anticancer drugs against CRC.